Association Between Junk Food Consumption Habits and Total Cholesterol Levels Among Employees of the Bengkulu Provincial Health Office - Faridah Faridah; Halimah Halimah; Jon Farizal (Jurnal Fatmawati Laboratory & Medical Science, 2026)
Background: Urban communities tend to consume junk food due to high levels of busyness and social activities. Junk food generally contains saturated fats that can increase total cholesterol levels and contribute to health problems such as hypertension, vascular obstruction, and heart disease. Low physical activity among office workers also contributes to increased cholesterol levels. Objective: This study aimed to analyze the relationship between junk food consumption habits, including consumption frequency and types of junk food consumed, and total cholesterol levels among employees of the Bengkulu Provincial Health Office. Methods: This study used a descriptive analytic design with a cross-sectional approach. The population consisted of 251 civil servants, with a sample size of 48 respondents selected through random sampling techniques. Dietary habits were measured using a Food Frequency Questionnaire (FFQ) and categorized into frequent and infrequent consumption based on median scores. Total cholesterol examination was performed using venous blood samples analyzed at the Medical Laboratory Technology Laboratory of Poltekkes Kemenkes Bengkulu. Data were analyzed univariately. Results: Most respondents were female (70.9%) with an average age of 46.4 years. A total of 52.0% of respondents frequently consumed junk food, while 64.6% had abnormal total cholesterol levels. Conclusion: The majority of respondents had abnormal total cholesterol levels, which were related to be associated with junk food consumption habits. These findings emphasize the importance of education regarding healthy dietary patterns as a preventive effort against elevated cholesterol levels among Health Office employees.